Front-of-Pack Labeling and the Nutritional Quality of Students' Food Purchases: A 3-Arm Randomized Controlled Trial. - Egnell, Manon; Boutron, Isabelle; Péneau, Sandrine; Ducrot, Pauline; Touvier, Mathilde; Galan, Pilar; Buscail, Camille; Porcher, Raphaël; Ravaud, Philippe; Hercberg, Serge; Kesse-Guyot, Emmanuelle; Julia, Chantal (American Journal of Public Health, 2019)
Objectives. To assess the effects of the Nutri-Score label (relative to the Reference Intakes label or no label) on the nutritional quality of students' food purchases. Methods. A 3-arm randomized controlled trial was conducted in France in 2017; 2907 participants were randomized into 1 of the 3 study arms (Nutri-Score, Reference Intakes, no label) and invited to purchase groceries from an experimental Web-based supermarket. The main outcome was the overall nutritional quality of purchases, measured according to a modified version of the Food Standards Agency Nutrient Profiling System (FSAm-NPS/HCSP) score. Results. The mean (±SD) FSAm-NPS/HCSP score was lower in the Nutri-Score group (2.02 ±3.56) than in the Reference Intakes group (2.69 ±3.44), reflecting higher nutritional quality; however, there was no significant difference between the Nutri-Score and no-label (2.45 ±3.28) groups or between the Reference Intakes and no-label groups. Shopping cart content was lower in calories and saturated fatty acids and higher in fruits and vegetables in the Nutri-Score arm than in the other arms. Conclusions. The Nutri-Score label appeared to improve the nutritional composition of students' food purchases relative to the Reference Intakes label or no label.